Value Creation in Art Galleries: A Service Logic Analysis. Issue 1 (February 2020) - Williams, Martin; Biggemann, Sergio; Tóth, Zsófia
This study addresses how non-profit organisations like art galleries participate in co-creating value to visitors (customers), providers, and other stakeholders, and how these processes can be conceptualised within a service logic framework. We evaluate how an art gallery touring exhibition in regional Australia contributed to customer value, drawing on data collected in 2014–2016 from publications and websites, and interviews with staff of art galleries and arts organisations. Our findings illuminated four forms of value creation: financial, knowledge sharing, social and cultural, and professional value. Country art galleries have strong visitor orientation and employ co-creation processes focused on enhancing visitors' experience, aligned with government directions on Indigenous understanding and objectives of local Indigenous art communities. However, customer value exchange is not well understood. The lack of marketing research expertise and usable visitor data is a barrier to value creation.